Adaptabilidad y estabilidad en el comportamiento de plantas de frijol comun - Laing, Douglas R. (International Center for Tropical Agriculture, 1978)
The concepts of adaptability and stability and their relative importance in beans are defined as well as the different methods used to measure them. Based on data submitted by the International Bean Yield and Adaptation Nursery (IBYAN) for 1976, different stability values were calculated using 3 different methods: (1) Finlay and Wilkinson`s regression analysis, (2) stochastic dominance analysis, and (3) combined variance analysis. When the former methods were applied to the IBYAN 76 data, a strong correlation was found between the values obtained and var. stability, indicating that the 3 selection criteria can be applied to the introductions to select the best materials. Four ideotypes of plants adapted to the different environment/cultivation systems combinations are also described. Information is given on the research conducted on the plant`s physiological aspects (sensitivity to photoperiod, tolerance to excess water in the soil, resistance or tolerance to drought, adaptation to temp., and stability in growth habit) which are the components of adaptation in beans. (CIAT)